Factors affecting profitability of sugarcane production as monoculture and as intercrop in selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2008)
The study was undertaken to know the profitability of sugarcane production as monoculture and as intercrop. Data were collected from 70 sugarcane growers of Daulatpur Upazilla under Kushtia District. Data were collected during the period from February to July 2003. The study reveals that the sugarcane plus potato combination produced the highest net return followed by sugarcane plus maize, sugarcane plus lentil and sole sugarcane production. Family labour cost, cost of urea, number of fertilizing, sowning/planting time of intercrop, cost of sett were the important factors which influence the profitability of sugarcane production both as intercrop and as nonoculture. High prices of inputs, lack of scientific knowledge, and dishonesty of officials are the major problems in sugarcane production. In order to promote intercropping in a large scale with sugarcane, government and other related organizations must encourage farmers to produce sugarcane as intercrop in order to earn higher net return. DOI: http://dx.doi.org/10.3329/bjar.v32i3.545Bangladesh J. Agril. Res. 32(3) : 433-444, September 2007